The experimental embryology and modern theories of ontogenesis - Cornejo, Ricardo H. (1942)
If the study of anatomy arouses admiration for the perfection of the structures, and the study of the physiology wonder by the correlation of the organic functions, the study of embryological process, covering both science is undoubtedly the biological problem more disconcerting how many men may arise